Divine Messengers in Genesis 18-19 and Ovid - Gnuse, Robert Karl 1947- (2017)
Stories of divine messengers who bring an announcement of an impending birth or a warning to escape destruction are found in Gen 18-19 and the writings of Ovid. Two sets of stories deserve close attention because of their great similarities. Three divine messengers promise a child to Abraham and Sarah and three Greek gods promise a son to Hyrieus in Ovids Fasti. Two divine messengers save Lot from the destruction of Sodom and two Greek gods save Philemon and Baucis from flooding in Ovid’s Metamorphoses. Perhaps the biblical author was familiar with the traditions used by Ovid.
Keywords: Bibel; Abraham; Baucis; Hyrieus; Lot; Ovid; Philemon